Interactive Bumper Animation pada Android untuk Meningkatkan Efektivitas Media Promosi - Triono, Maulid Agung; Adi, Dodot Sapto; Saudah, Saudah (Jurnal Nomosleca, 2021)
This study aims to describe the dynamics of educational promotion activities, by utilizing creative content that is technically continuously developed, so that information can be disseminated through the Android-based smartphone media. Technological innovation is an unavoidable demand, and is further enhanced along passing with regulation of The Minister of Education an Culture Number: 3-7 of 2020 concerning the function of the internet, that creative content whose dissemination relies on technological innovation will always make any higher education information more easily accepted by the public. IBA (interactive bumper animation), which is a creative content product, with a process based on the principle of integration of animation and video products, can be ascertained to be the best alternative to increase the effectiveness of promotional media. This research uses descriptive and applied approaches, involving informants who understand digital technology and its development, and nine main informants from the internal environment and three external supporting informants have been selected. The results of the research have been able to formulate an ideal concept for producing content, and then create a prototype that can be accessed via Android-based smartphone. Creative content development can be done by utilizing applications that can support promotional performance effectively, including Adobe Flash CS3 Professional, Adobe After Effects, Adobe Audition 6, Fruity Loop Studio, Edius7 and Adobe Premiere Pro. Keywords: Promotion Effectiveness; Android Smartphone, IBA (Interactive Bumper Animation)DOI :Â https://doi.org/10.26905/nomosleca.v7i1.5567